Effect of a patient-driven perioperative intervention on health literacy: A stepped-wedge cluster randomised sub-study - Ann Kristin Sandsbakk Austarheim; Kristin Harris; Hilde Valen Wæhle; Anette Storesund; Randi Julie Tangvik; Arvid Steinar Haugen (PLoS ONE, 2026)
We hypothesised that a patient-driven safety checklist would enhance patients’ health literacy. This study was conducted as a sub-study of a multicentre cluster trial with a stepped wedge design. Data were collected between March 2022 and February 2024. Healthcare personnel were partially blinded to group allocation and fully blinded to the health literacy questionnaire outcome. The study included seven surgical specialties (clusters) from a tertiary teaching hospital and two community hospitals in Norway. The patients were included from a pool within the cluster trial. In each of these seven clusters, 50 patients were randomly selected from 100 eligible patients both the control and the intervention group using a computer-generated randomisation procedure. This resulted in a total sample of 700 patients: 350 in each group, response rate 49.3%. Adults (≥18 years) undergoing elective surgery, fluent in Norwegian, living at home, and without cognitive impairment were included. Standard surgical information combined with a patient safety checklist consisting of items with instructions and information (medication safety, preparations, activity restrictions, complications, and follow-ups). The checklist was delivered preoperatively (≤ eight weeks). Controls received standard surgical information. No significant differences were observed in mean scores across the nine health literacy questionnaire outcome domains between the control and intervention groups. In this stepped wedge cluster trial, a preoperative patient safety checklist did not improve health literacy scores compared to standard care. Nevertheless, an interaction effect with time for the domain “Actively managing my health”, may indicate that the patient-driven checklist could support elective surgical patients’ health management. This finding aligns with qualitative feedback and warrants further investigation using larger samples and more sensitive and context-specific measurement tools. Trial registration: Registration date in the ClinicalTrials.gov, 20 March 2017, ID: NCT03105713 .